Presence of HLA‐DR Molecules and HLA‐DRB1 mRNA in Circulating CD4+ T Cells. (26th September 2016) - Revenfeld, A. L. S.; Steffensen, R.; Pugholm, L. H.; Jørgensen, M. M.; Stensballe, A.; Varming, K.
Abstract: The human major histocompatibility complex class II isotype HLA‐DR is currently used as an activation marker for T cells. However, whether an endogenous protein expression or a molecular acquisition accounts for the presence of HLA‐DR on T cells remains undetermined and still controversial. To further characterize this phenomenon, we compared several aspects of the presence of the HLA‐DR protein to the presence of associated mRNA ( HLA‐DRB1 ), focusing on human T cells from peripheral blood of healthy individuals. Using a flow cytometric approach, we determined that the HLA‐DR observed on CD4 + T cells was almost exclusively cell surface‐associated, while for autologous CD19 + B cells, the protein could be located in the plasma membrane as well as in the cytoplasm. Moreover, negligible expression levels of HLA‐DRB1 were found in CD4 + T cells, using an HLA‐DRB1 allele‐specific qPCR assay. Finally, the presence of HLA‐DR was not confined to activated CD4 + and CD8 + T cells, as evaluated by the co‐expression of CD25. The functional role of the HLA‐DR molecule on T cells remains enigmatic; however, this study presents evidence of fundamental differences for the presence of HLA‐DR on T cells from HLA‐DR in the context of antigen‐presenting cells, which is a well‐known phenomenon. Although an inducible endogenous protein expression cannot be excluded for the T cells, our findings suggest that a re‐evaluation of the HLA‐DR as a T cells activation marker is warranted.